The Impact of Corruption on External Debt in Nigeria: A Co-integration Approach (1996-2014) - Matthew, Abula; Mordecai D., Ben; Anda I, Ozovehe (Advances in Social Sciences Research Journal, 2016)
The study assessed the impact of corruption on the external debt in Nigeria for the period 1996 to 2014. The empirical analysis carried out using the co-integration technique revealed that Corruption Perception Index (CPI) which was used as a proxy for corruption and public expenditure (PEX) have significant positive relationship with external debt in the long-run and conform to our apriori expectations. However, in conformity to our apriori expectation, exchange rate (EXR) has a negative relationship with external debt in the long-run. The Vector Error Coefficient of concern showed that about 34.1479% of the errors will be corrected in the long-run, while the Granger Causality test indicated no causal relationship between the variables. It is therefore ascertained that so long as corruption persists unabated in the economy, they will be high level of external debt in the economy. Hence, the government should focus on the economic determinants of corruption, especially the policy of economic freedom (free market economy) to control the perceived level of corruption and must stop paying lip-service to the issue of combating corruption and match her words and commitment with actions by bringing defaulters to book, seizure of ill gotten assets and other corruption combating strategies so as to savage the nation from this monster.